2016
DOI: 10.1134/s1607672916040086
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression profile of mouse oligodendrocytes in inflammatory conditions

Abstract: In this study, we performed transcriptome profiling of oligodendrocyte culture of mice treated with the remyelinating therapeutic agent benztropine in the presence and absence of interferon gamma (IFNγ). The results of this work are important for understanding the expression profile of oligodendrocytes under conditions of systemic inflammation in the central nervous system in multiple sclerosis as well as the mechanisms of cellular response to benztropine in light of its possible use for the treatment of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Similar to our data, studies have reported alterations in proteins responsible for immune system processes and the cell cycle in benztropine treatment (Deshmund et al, 2013;Kudriaeva et al, 2016). Here, we identified ubiquitin and proteasome proteins related to the immune system (figure 1 and table S15).…”
Section: Antioxidant Defense and Stress Pathwayssupporting
confidence: 90%
“…Similar to our data, studies have reported alterations in proteins responsible for immune system processes and the cell cycle in benztropine treatment (Deshmund et al, 2013;Kudriaeva et al, 2016). Here, we identified ubiquitin and proteasome proteins related to the immune system (figure 1 and table S15).…”
Section: Antioxidant Defense and Stress Pathwayssupporting
confidence: 90%
“…The effect of benztropine on α-synuclein-overexpressing primary rat oligodendrocyte progenitor cells, utilizing transcriptome sequencing, was evaluated in Reference [ 14 ]. Recently, we reported transcriptome profiling of a primary culture of oligodendrocytes under inflammation conditions and remyelination stimulus, suggesting significant elevation of mRNA encoding catalytic subunits of immunoproteasome and major histocompatibility complex (MHC) class I molecules, which means increased capabilities of antigen presentation by IFNγ-treated oligodendrocytes [ 15 ]. In the present study, we aimed at analyzing the transcriptome of murine astrocytes in the background state, and to compare it with those under exposure to IFNγ, benztropine, or a combination of the two.…”
Section: Introductionmentioning
confidence: 99%